2017
DOI: 10.1177/1470593117708467
|View full text |Cite
|
Sign up to set email alerts
|

Contingent self-definition and amorphous regions

Abstract: This article explores the concept of contingent self-definition, whereby place brands employ flexible self-definitional approaches in constructing their place brand architecture. Adopting a view of regions as social constructs, the article builds on and extends previous work on place brand architecture by identifying the underlying factors that drive contingent self-definition decisions. Based on an empirical study of professionals tasked with managing region brands in the Netherlands, 11 factors are identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 83 publications
(132 reference statements)
1
22
0
Order By: Relevance
“…The place brands can be developed to represent a city, country or region (Dinnie, 2018). When a place brand communicates the country's identity to its target audience, it is called a country-brand.…”
Section: Country-brand Management Modelsmentioning
confidence: 99%
“…The place brands can be developed to represent a city, country or region (Dinnie, 2018). When a place brand communicates the country's identity to its target audience, it is called a country-brand.…”
Section: Country-brand Management Modelsmentioning
confidence: 99%
“…Spry et al (2020) confirm that with the development and growth of organizations and the increasing awareness of customers and consumers about the concept of quality and their awareness of their desires and requirements, the structure of brands has changed and tends to be a major organizational system linking brands with each other and contributing to forming organizational image among consumers. Dinnie (2017) indicated that regardless of the total and number of brands that the organization adopts or produces, the "how" of marketing, dealing and introducing these brands represents the most important and comprehensive idea in reaching customers and ensuring a higher market share for the organization. Thus, the brand architecture helps in defining the identity and identity of the brand and contributes to its development and design in a way that gives it more flexibility in order to expand the activities of the organization and obtain a higher market share (Dewhirst, 2017).…”
Section: Brand Architecturementioning
confidence: 99%
“…For some sub‐regional governments, a regional identity turns out to be a slogan for planning and regional development (Paasi 2009). For other local governments, a regional identity can be adopted as a ‘soft’ tool to promote social cohesion, regional marketing, and economic development (Dinnie 2017). Politicians and policymakers often face problems with collective identity narratives in regional policy debates (Allmendiger & Tewdwr‐Jones 2006).…”
Section: Literature Reviewmentioning
confidence: 99%